Trusting in God: Religious Inscriptions on Malay Seals - Gallop, Annabel Teh (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
Malay seals â€“ which can be defined as seals from Southeast Asia with inscriptions in Arabic script â€“ date from the 16th to the 20th centuries, and originate from all parts of Nusantara. The inscriptions on Malay seals serve to identify the seal owner through his (or her) name or title, often accompanied by a pedigree, date, and place name. About one-third of all Malay seals also include a religious legend, usually in the form of a pious expression, a supplication to God addressed by His Beautiful Names (al-asmÄâ€™ al-á¸¥usnÃ¡), or a quotation from the Qurâ€™an. This article demonstrates a striking degree of uniformity in the religious expressions found in Malay seals from all over the archipelago. Over half of these can be characterized as variations on a theme of al-wÄthiq billÄh, â€˜he who trusts in Godâ€™, but at the same time, there are also distinctive regional associations in different states in the archipelago with certain preferred phrases.